Strengthening Rules in The Institutional Network at The Regional Intelligence Community Forum (Kominda) in Preventing Potential Conflicts in Central Java Province - Sulaiman, Sulaiman; Ibrahim, Muh. Akmal; Sukri, Sukri (Journal of Neonatal Surgery, 2025)
The potential for conflict among the community in an area is an activity that must be monitored to identify potential conflicts early on, especially in Central Java Province. The role of intelligence is highly expected as an early warning system and strategic system to prevent this and the Central Java Province Regional Intelligence Community Forum ( Kominda ) is one part of the national security system. This research aims to analyze the rules in the institutional network at the Regional Intelligence Community Forum (Kominda) in preventing potential conflict in Central Java Province. This study used qualitative research methods. Data collection methods include observation, in-depth interviews, focus group discussions (FGD), and documentation studies. Data sources consist of primary and secondary data. Data analysis uses interactive data analysis methods. The informants in this research are actors who are directly involved in the interaction process of the Regional Intelligence Community Forum (Kominda) in preventing potential conflict in Central Java Province. The research results show that the rules in the Network at the Regional Intelligence Community Forum in efforts to prevent potential conflict in Central Java Province refer to Regulation of the Head of the Intelligence Agency Number 01 of 2014 concerning the Central Intelligence Community and Regional Intelligence Community. Follow-up activities on issues, problems, and conflicts that have been discussed at the Regional Intelligence Community Forum ( Kominda ) will be handed over to the respective institutional actors.